Le potentiel réflexif de la modélisation des environnements personnels d'apprentissage - Joris Felder (Centre National d'Enseignement à Distance, 2019)
Based on a language for modelling personal learning environments (PLE) of higher education students that we have developed (Felder, sous presse), this explorative research aims to evaluate the potential of PLE models of students generated by the researcher as an intermediate object between the student and himself (reflexivity). The Personal Learning Environment Modelling Language (MEPA) supported by a generic model of the PLE allows students' verbalized representations of their PLE to be visually objectified. A longitudinal study of 15 students validated the expressiveness of these PLE models and evaluated the reflexive potential of the models on students. Approached from the perspective of conceptual change theory, the study presented in this paper highlights the heuristic potential of models. The results show that students recognize the intelligibility, plausibility and fruitfulness of the modelling and that for some students, the objectification of their PLE has generated conceptual changes. This use of PLE models by learners could help to develop their autonomy, particularly by allowing them to recognize their person-plus.